Juvenile Glaucoma Related to Pineal Tumor Post Ventriculoperineal Shunt Procedure: A Case Report - Elan Satria; Fitratul Ilahi (HM Publisher, 2022)
Background: Glaucoma is a cause of irreversible blindness worldwide. This study aims to describe a case of juvenile open-angle glaucoma with a history of post-ventriculoperitoneal shunt perineal tumor. Case presentation: A 27 years old man came with complaints of blurred vision in both eyes about 2 years ago. The vision in both eyes is felt to be progressively decreasing, almost the same in both eyes. Blurred vision felt suddenly while driving 1 year ago. The patient had been diagnosed with a pineal tumor and underwent surgery to install a ventriculoperitoneal (VP) shunt for hydrocephalus indications 3 years ago. The patient also underwent radiotherapy 26 times for the treatment of the pineal tumor. Ophthalmological examination revealed 20/80 OD and OS vision; not advanced with pinhole, no eyelid edema, intraocular pressure OD 21 mmHg, OS 23 mmHg. Visual fields index on OD 85% and OS 81%. Central corneal thickness (CCT) examination showed CCT of the right eye at 541 mm and left eye at 547 mm. The results of a brain CT scan showed that there was a heterogeneous solid mass with calcification and cystic (necrotic) in the pineal region. This patient was diagnosed with juvenile glaucoma with bilateral papillary atrophy et causa pineal tumor post VP shunt. The therapy given was latanoprost 1 drop/day ODS and Cendo Lyteers 1 drop/6 hours ODS, and Thymol 0.5% 1 drop/12 hours ODS. Conclusion: Monitoring and evaluation of staging and clinical progression of glaucoma patients with increased intracranial pressure is a condition that needs attention. The correlation between the two is the involvement of the lamina cribrosa in the form of a translaminar pressure gradient.